Społeczno-gospodarcze i organizacyjno-prawne założenia zespołowych form produkcji rolnej w Polsce: [Socio-economic and organizational and legal prerequisites for collective forms of agricultural production in Poland] (Studia Prawnicze / The Legal Studies, 1963)
This article addresses four related issues: a) legal forms of collective farming in Poland in 1918-1939; b) the process of disintegration of the agricultural private-ownership production in the Polish People’s Republic; c) the process of integration of the agricultural production through the extensive development of simple forms of cooperation in agriculture; d) some organizational and legal issues of the highest form of integration of the agricultural production such as an agricultural production cooperative.a) The collective forms of agricultural production in Poland in 1918-1939 found support in the 1920 law on the implementation of the agrarian reform, in the decrees on the colonies of former soldiers and on the development of virgin lands. Based on it, there were peasant associations, agricultural cooperatives and agricultural production cooperatives. The livestock associations operated in Cieszyn Silesia according to the law adopted by the Silesian Sejm in 1933.b) According to the statistics of the Polish People’s Republic, there was an alarming gradual degradation of the individual farms caused by their increasing unbundling (especially in suburban and industrial areas), the ageing of the agricultural producers and the lack of young hands to work in agriculture.c) The process of integration in agriculture is carried out through the simple forms of agricultural cooperation in a narrow sense (various associations of production and consumer services which have no rights of a legal entity, as a rule, there are civil society partnerships) and the simple forms of cooperation in a broad sense (rural cooperatives, agricultural circles, forestry companies, etc., which have the rights of a legal entity).d) The highest form of integration of the agricultural production is represented by agricultural production cooperatives, the organizational and legal status of which is based on the 1961 law on cooperatives and their unions as well as on the fundamental provisions of the Charters made public by the Central Union of the Agricultural Cooperatives and binding on these cooperatives when they draw up or amend their Charters.